A demonstration device on chemical kinetics - Manguerra, Yolanda Tatlonghari
While Chemistry can usually be conveniently learned through laboratory activities, it has certain aspects that need additional elucidation in order to help the students "visualize", in one way or another, the processes involved and, in this manner, reach a better understanding of the concepts. Such "additional elucidations" usually involve the use of analogy or the use of a model. The objective of this paper is to present a device which, through analogy, is expected to illustrate the factors affecting rates of chemical reactions and chemical systems at equilibrium.